Organizational-Pedagogical Conditions for the Preparation of Future Primary School Teachers for Self-Learning - Kenesbekova, Saltanat; Dusembinova, Raifa; Mirza, Nataliya; Shayakhmetova, Marzhan; Alshynbayeva, Zhuldyz (Opción, 2019)
Currently, there is a significant increase in interest regarding issues related to self-learning by specialists, which is associated with the spread of new technology, rapid expansion of information, transition to an information so- ciety, and use of a competency-based approach in the training and profes- sional development of specialists. This has given relevance to the ideas of ongoing education, lifelong learning, and self-learning, which are expected to occupy a well-deserved place in pedagogical theory and practice. The research reported in this paper was aimed at analyzing some of the key ped- agogical conditions for preparation of future primary school teachers for self-learning. The paper explored the conceptual-theoretical foundations of preparing future primary school teachers for self-learning. In the study’s experimental part, the authors attempted to verify the hypothesis that the preparedness of future primary school teachers for self-learning activity can develop positive dynamics when the learning process is organized in a spe- cial way and appropriate organizational-pedagogical conditions are created for that. Based on the findings from this study and the results from a peda- gogical experiment, the authors identified a set of organizational-pedagogi- cal conditions and formulated a set of practical recommendations regarding the preparation of future primary school teachers for self-learning activity.